A preliminary study of the application of the strain-self-sensing smart geogrid rib in expansive soils. Issue 1 (February 2023) - Bi, Gang; Yang, Shaohua; Wu, You; Sun, Yijie; Xu, Hongzhong; Zhu, Bingkun; Huang, Chunxia; Cao, Suqian
Abstract: Flexible conductive materials are widely used in structural health monitoring; it is also known in geotechnical engineering. In this preliminary study, a strain-self-sensing smart geogrid rib was proposed to monitor the induced strain by wetting-drying cycles of the expansive soil. After the calibration, a physical modeling test was conducted with the smart geogrid rib reinforced in expansive soils under three wetting-drying cycles. Results demonstrated: that the smart geogrid rib was capable of self-sensing its strain; the strain self-sensed by the smart geogrid rib was in good agreement with that measured by FBG strain sensors before cracks were generated; it could capture the crack propagation of expansive soils during wetting-drying cycles by the discrepancy compared to FBG sensors. Further study will be continued for the mechanism of the geogrid instead of the geogrid rib and the application to real-time monitoring of the performance of the geosynthetic expansive soil slopes. Highlights: A geogrid rib was fabricated with flexible conductive materials to make the strain-self-sensing possible. A physical modeling test was conducted to demonstrate the application of the smart geogrid rib in the expansive soil. The geogrid rib could sense the crack propagation of expansive soils, and strains measured agreed with strain sensors.